Kajian Teologis Memberi Sedekah Secara Tersembunyi Dan Implikasinya Bagi Orang Percaya (International Forum of Researchers and Lecturers, 2023)
The Lord Jesus taught His disciples during the sermon on the Mount, it was his teaching about being someone who would care about what they were struggling with at that time, based on the Gospel of Matthew 5-7. In Bible dictionaries, almsgiving is a source of material support for the poor and destitute whom almost no one knows. When giving alms, don't know what your left hand is doing with your right hand, because giving alms is everyone's duty. So, giving alms means doing justice, because alms is not a voluntary gift from the rich to the poor, but a religious obligation.